2014
DOI: 10.2478/s11772-014-0190-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 905 nm and 1550 nm semiconductor laser rangefinders’ performance deterioration due to adverse environmental conditions

Abstract: Laser rangefinder performance (i.e., maximum range) is strongly affected by environment due to visibility-dependent laser attenuation in the atmosphere and target reflectivity variations induced by surface condition changes (dry vs. wet). Both factors have their unique spectral features which means that rangefinders operating at different wavelengths are affected by specific environmental changes in a different way. Current state of the art TOF (time of flight) semiconductor laser rangefinders are based mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 7 publications
0
66
0
1
Order By: Relevance
“…Various recent studies have investigated the effect of weather on different wavelengths of LiDAR, particularly of rain and fog. The effect on both wavelengths is similar, as at the same optical power there is a small difference (<10%) between the two [71]- [72].…”
Section: A Wavelengthsmentioning
confidence: 70%
“…Various recent studies have investigated the effect of weather on different wavelengths of LiDAR, particularly of rain and fog. The effect on both wavelengths is similar, as at the same optical power there is a small difference (<10%) between the two [71]- [72].…”
Section: A Wavelengthsmentioning
confidence: 70%
“…However, this solution is of limited use, because of constraints such as high cost and high energy usage. The loss of efficiency due to adverse environmental conditions was examined in [ 123 ], and a comparison was made between lidars with wavelengths 905 nm and 1550 nm. The findings of [ 123 ] have also shown that lasers with a wavelength of 1550 nm have a much higher water absorption compared to 905 nm lidar.…”
Section: Sensorsmentioning
confidence: 99%
“…The classic sensing systems increasing the safety of car operation include: tire-pressure monitoring system (TPMS), adaptive cruise control (ACC), blind-spot detection (BSD), lane-departure warning (LDW), traction control (TC) sometimes called rollover prevention, antilock braking system (ABS), emergency brake assist (EBA), adaptive headlights and rearview camera. All these systems are well developed, but the progress in technology and system performances are under continuous improvements [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%